2015
DOI: 10.5505/tjtes.2015.72173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Types of Proximal Femoral Nails in the Treatment of Intertrochanteric Femur Fractures

Abstract: BACKGROUND: Hip nailing is frequently used to treat unstable intertrochanteric femoral fractures (ITF) in elderly patients. In this retrospective study, we compared the functional and radiological results, and the complications, of patients treated using proximal femoral nails (PFN) with an integrated, interlocking, compression lag screw, or two separate lag screws, which allow linear compression at the fracture site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…[16] The results of a study that compared PFN with 1 and 2 lag screws showed that 2 lag screws yielded better results in patients with good bone quality but had a higher cut-out risk in patients with osteoporosis. [17] Uzer et al [18] compared functional and radiological results as well as complication rates in patients treated with PFN using an integrated, interlocking, compression lag screw and 2 separate lag screws. They found no statistically significant differences in the functional and radiological results or complication rates in the treatment of intertrochanteric femur fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The results of a study that compared PFN with 1 and 2 lag screws showed that 2 lag screws yielded better results in patients with good bone quality but had a higher cut-out risk in patients with osteoporosis. [17] Uzer et al [18] compared functional and radiological results as well as complication rates in patients treated with PFN using an integrated, interlocking, compression lag screw and 2 separate lag screws. They found no statistically significant differences in the functional and radiological results or complication rates in the treatment of intertrochanteric femur fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion rate was 87-100 %, the nonunion rate was 3-13%, malunion rate was 3-6%, and implant failure rate was 0-4% in the first and second generation CMNs [9,11]. The disadvantages of IMNs were the high frequency of need for intraoperative fluoroscopic imaging, difficulties in techniques in implementation, the need for experienced surgeons, the difficulty in implant removal in need, and implantation difficulty especially in fractures extending trochanter major and fossa piriformis [7,9,10,12]. High level of complication rates after surgical fixation in unstable proximal femur fracture in elder patients brought up primary hip prosthesis implementation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 60, but the age interval was 19-90. In the surgical method of implant selection in unstable proximal femur fractures, many treatment methods were suggested in the past, and there were still discussions about that [2][3][4][7][8][9][10]. In one of them that is 95 degree wedged condylar plates, fusion rate had been found 92-100 %, malunion was 13-24%, the late union was 6-19%, nonunion was 3-12%, and implant failure was 6-24% [9].…”
Section: Discussionmentioning
confidence: 99%
“…PFs are surgically treated with a closed reduction and internal fixation (CRIF) osteosynthesis by a cervical-cephalic nail or a sliding hip screw [5][6][7][8][9][10][11][12][13]. Intramedullary nail is the preferred synthesis because it allows a reduction of the time of surgery, a stable synthesis and an early patient mobilization [14]. In particular, these considerations are valid for more stable PFs, classified with AO/OTA [15] pattern 31-A1 (pertrochanteric simple) and 31-A2 (pertrochanteric multifragmentary).…”
Section: Introductionmentioning
confidence: 99%